2012
DOI: 10.1289/ehp.1104242
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Evidence-based Asthma Interventions in Post-Katrina New Orleans: The Head-off Environmental Asthma in Louisiana (HEAL) Study

Abstract: Background: Childhood asthma morbidity and mortality in New Orleans, Louisiana, is among the highest in the nation. In August 2005, Hurricane Katrina created an environmental disaster that led to high levels of mold and other allergens and disrupted health care for children with asthma.Objectives: We implemented a unique hybrid asthma counselor and environmental intervention based on successful National Institutes of Health asthma interventions from the National Cooperative Inner City Asthma (NCICAS) and Inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…ajph.org) describes the methods standards deployed and the accompanying strategy to achieve those standards; many of these pertain to the overall HEAL Study components described extensively in previous publications. 7,8,19 Methods most directly applicable to the current investigation are discussed more specifically in the following subsections, in the context of the specific aims outlined in this section.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…ajph.org) describes the methods standards deployed and the accompanying strategy to achieve those standards; many of these pertain to the overall HEAL Study components described extensively in previous publications. 7,8,19 Methods most directly applicable to the current investigation are discussed more specifically in the following subsections, in the context of the specific aims outlined in this section.…”
Section: Methodsmentioning
confidence: 99%
“…Results from home assessments and a successful environmental asthma counselor intervention are reported elsewhere and are summarized in the following paragraph. [7][8][9] HEAL demonstrated that an evidencebased environmental asthma counselor intervention can be implemented in a postdisaster setting to improve asthma management and assess environmental exposures. We used a novel combination of the efficacious National Cooperative Inner-City Asthma Consortium (NCICAS) asthma counselor intervention 10 and the Inner-City Asthma Study (ICAS) environmental intervention 11 to intervene on 182 participants enrolled in the HEAL Study.…”
mentioning
confidence: 99%
See 3 more Smart Citations